2014
DOI: 10.11646/zootaxa.3835.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomical study on the mollusks collected in Marion-Dufresne (MD55) and other expeditions to SE Brazil: the Fissurellidae (Mollusca, Vetigastropoda)

Abstract: The Fissurellidae collected by the Marion-Dufresne Expedition, as well as other regional expeditions to SE Brazil are examined taxonomically, treating 21 species, of which 20 are new. The following new species are described (order according to depth range; species marked with * are from expeditions other than MD55): Cornisepta uirapa (790-940 m), Cornisepta arrepiata (295-1,050 m), Cornisepta aninga (295-1,050 m), Cranopsis hycavis (637 m), Cranopsis nymphalis (295 m), Cranopsis enigmatica (790-940 m), Cranops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This is not unprecedent, since several papers based totally or partially on MD55 material reported the presence of genera and species of gastropods previously unrecorded in the Southwestern Atlantic (e.g., Fernandes et al, 2013;Simone & Cunha, 2014;Salvador et al, 2014;Cavallari et al, 2019;Fernandes & Pimenta, 2020). Significant range expansions of over 1,000 km have also been frequently reported in these studies (e.g., Cavallari et al, 2014;Salvador et al, 2014;Simone & Cunha, 2014;Cavallari et al, 2019). In many cases, the new records leave large occurrence gaps (e.g., some species recorded in the Caribbean and off southeastern Brazil, as in I. oryza).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is not unprecedent, since several papers based totally or partially on MD55 material reported the presence of genera and species of gastropods previously unrecorded in the Southwestern Atlantic (e.g., Fernandes et al, 2013;Simone & Cunha, 2014;Salvador et al, 2014;Cavallari et al, 2019;Fernandes & Pimenta, 2020). Significant range expansions of over 1,000 km have also been frequently reported in these studies (e.g., Cavallari et al, 2014;Salvador et al, 2014;Simone & Cunha, 2014;Cavallari et al, 2019). In many cases, the new records leave large occurrence gaps (e.g., some species recorded in the Caribbean and off southeastern Brazil, as in I. oryza).…”
Section: Discussionmentioning
confidence: 96%
“…The expedition recovered numerous deep-water mollusks from the southeastern Brazilian coast. Most of this material remained unstudied for years, but recent efforts have been steadily changing this scenario, e.g., comprehensive reports on Triphorinae (Fernandes et al, 2013), Naticidae (Simone, 2014), Fissurellidae (Simone & Cunha, 2014), Seguenziidae (Salvador et al, 2014), and Calliostomatidae (Cavallari et al, 2019). The present work focuses on a small assembly of species belonging to the cerithioidean families Cerithiidae, Litiopidae, Modulidae and Planaxidae.…”
Section: Introductionmentioning
confidence: 99%
“…None of the eight western Atlantic species of Cranopsis described and illustrated by Simone & Cunha (2014) is identical to Puncturella agger. Cranopsis canopa Simone & Cunha, 2014 is somewhat similar in profile and in having a relatively small septum, but it differs from P. agger in having fewer and broader axial ribs (46 versus up to 90 in P. agger), uniform axial ribs (P. agger usually has larger and smaller ribs intercalated), and the ventro-anterior edge of the septum concave, while in P. agger it is convex.…”
Section: Remarksmentioning
confidence: 94%
“…Studies on sediment samples from Canopus collected in 2005 have revealed a remarkable number of new taxa. This includes 17 new gastropod species belonging to 12 different families, most of which were described based on empty shells (e.g., Abbate & Cavallari, 2013;Simone & Cunha, 2014;Fernandes et al, 2015). In the present study, we formally describe a new species of Arene from Canopus stemming from a broader review of the local vetigastropod fauna (Cavallari & Simone, unpublished data).…”
Section: Introductionmentioning
confidence: 99%